Lexical And Semantic Processes in The Modern Russian Language (Texas Journal of Philology, Culture and History, 2021)
So far, most languages have changed a lot. We can see these alterations in the lexical and semantic features of different languages. This article is dedicated to lexical and semantic processes in the modern Russian language